Lasten ja nuorten luonnossa liikkuminen ja sen yhteys mielen hyvinvointiin : LIITU 2022 -tutkimuksen tuloksia - Varis, Susanna (2024)
Green exercise means physical activity in a natural or partly built environment. Green exercise has been found to be associated with mental well-being, such as improved mood, and self-esteem, and lower levels of stress. Additionally, green exercise has been found to improve well-being of young people, particularly during the Covid 19-pandemic. The aim of this thesis was to find out how much 5th, 7th and 9th graders exercise and spend their leisure time in natural environments and how grade, gender, place of residence and family affluence are associated with green exercise. The aim was also to find out how green exercise was associated with mental well-being in young people.